Effect of Bi-doped on structural, morphological, and electrical properties of Sb₂O₃ nanostructured thin films for solar cells applications - Hussien, Mustafa K.; Khodair, Ziad T.; Kamil, Asaad A.; Salman, Sabah A. (Edelweiss Applied Science and Technology, 2025)
Undoped and Bi-doped Sb₂O₃ nanostructured thin films (3%, 5%, 7%, 9%) were prepared by chemical spray pyrolysis on glass substrates at 350°C. XRD confirmed polycrystalline cubic structure with (111) orientation, while FE-SEM revealed doping effects on surface morphology. investigation revealed that film surfaces had a cubic-like nanostructure. The results of the electrical properties showed that, depending on the Hall effect, that p-type nature of all thin films. Solar cells with the composition (Sb2O3/n-Si), which contains a layer of Sb2O3 undoped and doped with Bi at a ratio of 9%, were prepared and investigated in dark and lighting conditions at room temperature for the heterojunction. The obtained results demonstrated that the value of the reverse current of the heterojunction (doped and undoped- Sb2O3/n-Si) under illumination at a specific voltage is higher than that in the dark. This study aims to synthesis undoped Sb2O3 films and doped with bismuth (Bi) at different ratios (3, 5, 7, and 9%) using the chemical spray pyrolysis technique and study structural, and electrical properties to get the optimum condition for fabricating solar cells and study its characteristics of the photovoltaic measurements (ISC, VOC, FF, h).